Inovasi Es Krim Tape Sukun Dengan Penambahan Sari Koro Pedang Dan Bit Sebagai Pewarna Alami - Majidah, Amanda; , Dra. Aminah Asngad, M.Si (2015)
Ice cream is a semi-solid food made by freezing a mixture of milk, fats of an animal and vegetable, sugar and other foodstuffs. In this research used cow milk, extract jackbean, breadfruit tape and extract beet. This research aims:determain the content of soluble protein, the speed of malted ice cream, and organoleptic test of breadfruit tape ice cream with the addition extract jackbean and extract beet.soluble protein content was measured using the method Lowry. The study designed using factorial Comlpetely Randomized Design with 2 factors:factor 1: extract jackbean :cow milk rasio 0:100(K0), 40:60(K1), 50;50(K2) and factor 2: extract beet 10%(P1), 8%(P2), 6%(P3)with 3 replications from each treatment.the results showed that the highest soluble protein (formulatios 50% extract jackbean, 50% cow milk, 20% breadfruit tape and 10% extract beet)to reach 0,700% soluble protein content. Treatment K0P3(formulatios 0% extract jackbean, 100% cow milk, 20% breadfruit tape and 6% extract beet) have highest melted speed during 1619,3seconds. Treatment K0P1(formulatios 0% extract jackbean, 100% cow milk, 20% breadfruit tape and 10% extract beet)have pink color, savory aroma, sweet taste, soft the texture and most preferred by consumers.